PRACTICE OF USING INHALED PREVENTIVE ASTHMA MEDICATION AMONG PARENTS OF PEDIATRIC PATIENTS AT VIETNAM NATIONAL CHILDREN'S HOSPITAL IN 2023 AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to describe parental practices in administering preventive inhaled medications and identify factors associated with correct technique among caregivers of asthmatic children at the National Pediatric Hospital in 2023.Methods: A cross-sectional descriptive study with analytical components was conducted among 209 parents and caregivers of asthmatic children attending the International Center S and the Department of Immunology and Allergy. Data were collected using structured questionnaires and observational checklists. Descriptive and inferential statistics were performed using SPSS 22.0, with a significance level set at p < 0.05.Results: 72.7% demonstrated correct inhaler technique. The lowest accuracy rates were observed in exhalation before inhalation (58.9%) and pressing the canister during inhalation (32.5%). Parental occupation was significantly associated with inhaler technique (p < 0.05); farmers were 3.17 times more likely to perform incorrectly compared with civil servants. Conclusion: Although most parents correctly administered preventive inhalers, coordination errors remain common. Continuous educational interventions and hands-on training are essential to improve parental technique and optimize asthma control in children.